Efeitos dos antibióticos de uso pecuário associados à agua residuária de suinocultura sobre a atividade microbiana do solo - Kessler, Nathalie Caroline Hirt (2017)
Antibiotics are added to animals’ diet to increase zootechnical development rates in livestock production. Thus, tetracycline class drugs are the most frequently used ones, mainly in swine breeding. It is known that these compounds are not completely digested by the animals’ metabolism, consequently, they take part of wastewater, and eventually, they can reach the soil and change all the dynamics of microorganisms. Thus, this trial aimed at evaluating the effect of tetracycline associated with swine wastewater on enzymatic activity of soil regarding biogeochemical cycle of nutrients under two applications, in different seasons. The experiment was carried out in soil-containing pots, which received, once in summertime, and again in the autumn, doses of swine wastewater (0.2 and 0.3 L) with or without tetracycline doses (35 μg L-1), chlortetracycline (40.9 μg L-1) and doxycycline (14.9 μg L-1). Soil samples were collected at 2, 4, 8, 15, 30, 45 and 75 days after each application of the treatments in order to determine dehydrogenase, β-glucosidase, acid phosphatase and urease enzymes activity. It was observed an increase in the activity of all the studied enzymes when submitted to swine wastewater. And, a decrease of their activity when in antibiotics presence, applied in both experimental periods. There was also a decrease in nutrients bioavailability in soil, which reduces soil quality and fertility